Manajemen Sarkopenia - Yunita, Sri (Journal of Telenursing (JOTING), 2025)
This study aims to improve understanding of sarcopenia and develop effective strategies to prevent, diagnose, treat, or manage sarcopenia. The method used is descriptive-analytical in the form of a case study. The study results indicate that the management of sarcopenia uses two main principles, namely physical exercise intervention and nutritional intervention. Physical exercise 3-4 times a week for 3 months will show significant muscle mass and strength changes in sarcopenia patients. Providing protein in the form of leucine-enriched protein or whey is very effective in increasing muscle mass. Increasing protein intake by 1.2 grams/kg BW/day is recommended in patients with sarcopenia. In conclusion, sarcopenia often occurs in the elderly, which causes mobility disorders. Sarcopenia management that can be done today is a combination of physical activity, especially resistance training, and fulfillment of nutritional adequacy, including protein, vitamins, and minerals. Keywords: Management, Aging, Sarcopenia